24.2k views
0 votes
Solve the equation.
y + 6 = -3y + 26
y = -8
y = -5
O y = 5

User Jon Tirsen
by
5.1k points

2 Answers

7 votes

Answer:

y = 5

Explanation:

Simplifying

y + 6 = -3y + 26

Reorder the terms:

6 + y = -3y + 26

Reorder the terms:

6 + y = 26 + -3y

Solving

6 + y = 26 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.

6 + y + 3y = 26 + -3y + 3y

Combine like terms: y + 3y = 4y

6 + 4y = 26 + -3y + 3y

Combine like terms: -3y + 3y = 0

6 + 4y = 26 + 0

6 + 4y = 26

Add '-6' to each side of the equation.

6 + -6 + 4y = 26 + -6

Combine like terms: 6 + -6 = 0

0 + 4y = 26 + -6

4y = 26 + -6

Combine like terms: 26 + -6 = 20

4y = 20

Divide each side by '4'.

y = 5

Simplifying

y = 5

User Boland
by
4.8k points
5 votes

Answer:

y=5

Explanation:

y+6=-3y+26

first you should collect the like terms

y+3y =26-6

now you should add and subtract

4y=20

yah you should divide by both sides by 4 so that we can have the value of y

4y=20

4 4

y=5

User UltimoTG
by
4.8k points